Microthermic Observations in Arctic Vegetation. - Hansen, Kjeld (Meddelelser om Grønland, 1973)
In July-August 1965 concurrent microthermic measurements were made at 4 stations in the low-arctic South Greenland (3 in the lowland and 1 in the mountains 610 m a. s. l.) on several biotopes varying in altitude a. s. I., exposure, and vegetation; a transportable thermistor and several stationary thermometers were used in the process. Measurements of daily maxima and minima on the surface of the ground show a close correlation with macroclimatic conditions, exposure, and type of vegetation. In various southward-facing types of scrubs in the lowland maxima up to 52°-57° C were measured in clear weather. Under overcast, possibly rainy conditions the maxima are much lower, especially on northward-facing biotopes (most frequently 20°-25°). Observations of microthermic gradients above ground and below ground (from -10 cm to + 200 cm) show, however, that these extreme maxima mainly occur in the lower layers of the vegetation (5-10 cm), where the vertical difference can be very high (10°-20° C). Evidently, under favourable macroclimatic conditions approximately the same microthermic conditions can prevail in the mountain (610 m a. s. I.) as in the lowland (maximum up to 48° C), whereas when the weather is unfavourable the temperature in the mountain is distinctly lower (8° C).